184k views
2 votes
Need help please thanks

Need help please thanks-example-1
User Danikov
by
6.7k points

1 Answer

1 vote

Answers: (a→b), (b→a), (c→c)

Step-by-step explanation:

Column A:

a)
y = -3x + (1)/(3)

m = -3 ⇒ m⊥ =
(1)/(3)


b) 6x - 2y = 4

-2y = -6x + 4

y = 3x - 2

m = 3 ⇒ m⊥ =
-(1)/(3)


c) y - 3 =
(1)/(3)(x - 3)

m =
(1)/(3) ⇒ m⊥ = -3


Column B

a) y - 3 =
-(1)/(3)(x - 3)

m =
-(1)/(3)


b) y =
(1)/(3)x + 6

m =
(1)/(3)


c) 3x + y = 3

y = -3x + 3

m = -3

******************************************************************************

Column A letter a matches to Column B letter b

Column A letter b matches to Column B letter a

Column A letter c matches to Column B letter c


User Ansel
by
5.7k points